Preparing students to respond: A pilot study to explore whether Mask-Ed simulation can assist students in developing clinical judgment - Jane S Frost; Kathryn Sainsbury; Christine Waller
Clinical judgment is a key component of 'thinking like a nurse'(Tanner, 2006). This pilot project uses Mask-Ed™ simulation in conjunction with Tanners (2006) Clinical Judgment Model to explore clinical judgment in a pre-clinical workshop. Method: a cross sectional survey was conducted with third year nursing students enrolled in one unit of study. Results: The confidence of students to respond to a patient, one of the four domains of clinical judgment (Tanner, 2006) was increased. Conclusion : Mask-Ed™ when used in a pre-clinical workshop shows the potential to positively affect the student nurses ability to respond to a patient cues, a key part of patient care and the development of clinical judgment.